2004
DOI: 10.1097/01.aog.0000135277.04565.e9
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Antenatal Depression and Anxiety for Obstetric Outcome

Abstract: There is an association between antenatal depressive and/or anxiety disorders and increased health care use (including cesarean deliveries) during pregnancy and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
195
2
20

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(235 citation statements)
references
References 24 publications
18
195
2
20
Order By: Relevance
“…A previous study (Chung et al, 2001) reported that depression in late pregnancy was associated with an increased risk of epidural analgesia, operative deliveries (cesarean sections and instrumental vaginal deliveries) and supported by another study (Andersson et al, 2004) which found that planned cesarean delivery and epidural analgesia during labour were also significantly more common in women with antenatal depression and/or anxiety.…”
Section: A Fadzil Et Almentioning
confidence: 76%
“…A previous study (Chung et al, 2001) reported that depression in late pregnancy was associated with an increased risk of epidural analgesia, operative deliveries (cesarean sections and instrumental vaginal deliveries) and supported by another study (Andersson et al, 2004) which found that planned cesarean delivery and epidural analgesia during labour were also significantly more common in women with antenatal depression and/or anxiety.…”
Section: A Fadzil Et Almentioning
confidence: 76%
“…Only among women with history of repeated sexual victimization and those struggling with depression and trauma symptomology (not mutually exclusive categories) did fear levels begin to show significant elevations. There is prior evidence for a relationship between anxiety and depression and fear of childbirth [8,26], and sexual assault and fear of childbirth [1]; the current work suggests that depression mediates the relationship between these negative personal experiences and childbearing fear. Negative expectations and fear regarding childbirth may be rooted in belief systems associated with depression (e.g.…”
Section: Discussionmentioning
confidence: 56%
“…Excessive childbearing fear is a concern given its relationship with increased healthcare utilization [8,9], complicated birth [10,11], and increased risk for instrument-assisted or operative deliveries [1,5,12]. Fear of childbirth is a topic that has received little objective investigation in American women despite its influence on maternal request cesarean sections [12][13][14][15], which have increased in the U.S., the controversy surrounding these requests [16][17], and concern about the lack of information suggesting how providers attend to serious childbirth fear.…”
Section: Introductionmentioning
confidence: 99%
“…For women, these include non-compliance with prenatal care and with healthy life styles [13], spontaneous abortion [14], preeclampsia, [15] and complicated deliveries [16].…”
Section: Secondmentioning
confidence: 99%